Monitoramento e avaliação de condições adversas em ciclovias através de multi-sensoriamento por bicicletas e processamento de dados urbanos - Oliveira, Franklin Lázaro Santos de (2021)
Investments in mobility and sustainable transport are a trend in large cities, mainly due to the fact that traditional vehicles are expensive, inefficient in transporting people, and large polluters. At the same time, people have become more likely to seek for cleaner and healthier options for medium and short distance travel, which has also boosted the adoption of bicycles in urban areas. Faced with these changes in the behavior of the population, government agencies have been paying attention to issues of basic infrastructure, such as the construction of bike paths and the reorganization of the road network, in order to allow cyclists to travel safely. However, in order to assess the quality of cycle paths that is perceived by cyclists, a comprehensive mechanism must be implemented that incorporates different factors that can negatively impact the safety and health of cyclists, such as air pollution, risk of accidents, noise pollution, excessive sun exposure, low humidity, among others. In this context, this work proposes a new solution for monitoring, evaluation and visualization of the quality of cycle paths in order to inform cyclists about the conditions of the paths and guide governments to improve and implement new cycle paths, employing for that embedded sensing technologies, distributed data processing functions, fuzzy-based quality assessment, and a specialized networking architecture. This comprehensive multi-level solution is carefully specified and simulated on real scenarios, providing promising results that can better support the adoption of sustainable cycling in modern cities.